"Expect the Unexpected:" Experiences of U.S.-Trained Student Affairs Professionals Working Abroad. Issue 2 (14th March 2020) - Witkowsky, Patricia
Abstract : Opportunities for student affairs work outside of the United States continue to increase because of the value of the U.S. student affairs model in the growing number of branch campuses and U.S.-inspired institutions. This qualitative study explored the student-focused and institutional experiences of 29 student affairs professionals abroad. The findings include a recognition of the universality of student needs, the applicability of student development theory in a global context, and unique positions and organizational structures abroad.